Decrease in the effectiveness of valproic acid against the background of antibacterial therapy with imipenem/cilastatin in pediatric practice: A case report - A. B. Strok; M. S. Chenkurov; M. N. Kostyleva; D. A. Umutkuzina (Сибирский научный медицинский журнал, 2024)
A clinical case of the co-medication of valproic acid and cilastatin/imipenem in a 17-year-old girl with generalized tonic-clonic seizures is described. As an antiepileptic therapy, the child was prescribed valproic acid, the concentration of which in the blood plasma was more than 80 µg/ml, and seizures were not observed during this therapy. At the same time, due to the developed pneumonia, the girl was imipenem/cilastatin prescribed. Co-medication of drugs led to a decrease in the concentration of valproic acid in the blood plasma less than 50 µg/ ml, relapse of epileptic seizures was noted. Correction of antiepileptic therapy with phenobarbital did not lead to the seizure control. The removal of imipenem/ cilastatin contributed to the increase in the concentration of valproic acid in blood plasma above 50 µg/ ml, which corresponds to the recommended therapeutic range. Within two weeks after discontinuation of imipenem/ cilastatin, the concentration of valproic acid reached values as close as possible to the values before the start of antibiotic therapy. The authors of the article concluded that it is necessary to conduct therapeutic drug monitoring in children receiving valproic acid and imipenem/ cilastatin (antibiotic of carbapenem group), based on the known mechanisms of pharmacokinetic interaction.